Effectiveness of Evaluation of Moral Creed Learning on Student Learning Achievement at Madrasah Ibtidaiyah Al-Inayah Cijambe (Lembaga Pengembangan Kinerja Dosen, 2024)
The main aim of this research is to find out how effective the evaluation of Moral Creed learning is on student learning achievement at Madrasah Ibtidaiyah Al-Inayah Cijambe. To complement this thesis, the author uses qualitative and descriptive research with a pedagogical approach. Research on problem disclosure as in data analysis using observation, interviews and use of documents using data analysis, data reduction, data presentation, drawing conclusions and data verification. The results of this research are shown in the planning for the evaluation of Aqidah Akhlak learning at Madrasah Ibtidaiyah which was carried out in the form of determining evaluation objectives, compiling grids, writing questions and analyzing and revising questions. The techniques for implementing Aqidah Akhlak learning evaluation are carried out in the form of written tests, oral tests and non-tests.